Optimization of a servo motor manufacturing value stream by use of 'Industrie 4.0' - Abersfelder, Sandra; Heyder, Andreas; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
'Industrie 4.0' establishes multidirectional ways of cross-linking in the production area. Therefore, a complex integration of horizontal and vertical interactions has to work hand in hand. A closer look into present production shows a huge amount of optimization potentials on the way to a 'Smart Factory' with high product variability. Hence, one of the next milestones for production is to create a virtual image of the real products in the manufacturing execution system (MES) in order to have a gapless traceability and an extensive storage of process data along the whole value chain. Especially data mining will gain importance to scan information for meaningful correlations or creating configuration rules as well as decisions for subsequent process steps. For a servo motor production the implementation of a magnetic field measurement of rotors is an opportunity to gather data for data mining. In addition to that, other interesting benefits are expected in failure detection, quality improvement and an increase in performance. To evaluate the different mentioned areas of activity, a pilot test series is planned. It will also provide data sets for a first data mining investigation. The concept of the first rotor measurement test procedure is presented in the following.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 'Industrie 4.0'; Magnetization; Servo Motors